Increase consumers’ willingness to pay a premium for organic food in restaurants: Explore the role of comparative advertising - Yu, Weiping; Han, Xiaoyun; Cui, Fasheng (Frontiers in Psychology, 2022)
Offering organic food is a new trend in the hospitality industry seeking sustainable competitiveness. Premiums and information barriers impede continued growth in organic consumption. This study aims to explore the role of comparative advertising (CA) in organic food communication. Three empirical studies were used to verify the effect of CA (vs non-comparative advertising (NCA)) on consumers' WTPP for organic food, examining how benefit appeals (health vs environmental) and consumers' organic skepticism affects CA. The results indicate that matching CA and health appeals increase consumers' WTPP, while environmental appeals have no significant differences between the CA and NCA groups (Study 1). Information persuasiveness mediates the interaction between CA and benefit appeal on WTPP (Study 2). Comparative advertising increases WTPP among consumers with high organic skepticism, while the interaction between CA and health appeal is only effective for low skepticism consumers (Study 3). The findings unravel and explain the mechanics of how CA works in organic products, which can help restaurants, retailers and tourist destinations advertise organic food to increase consumers' WTPP.